Complement membrane attack complex is related with immune-mediated necrotizing myopathy - Cong, Lu (e-Century Publishing Corporation, 2014)
This study is to investigate the expression of complement membrane attack complex (C5b-9) in the skeletal muscle of patients with necrotizing myopathy (NM), and to investigate the relationship between C5b-9 and NM. Thirteen patients with NM and control patients with polymyositis and muscular dystrophy were enrolled in this study. Examinations including creatine kinase (CK) and L-lactate dehydrogenase (LDH) in the serum, electromyogram and muscle pathological examination were performed. C5b-9 expression in the skeletal muscle was determined by immunohistochemistry and analyzed by Image Plus Pro 6.0. C5b-9 expression was particularly prominent in necrotic muscle fibers, and also positive in blood vessels. C5b-9 diffusely expressed in vascular endothelial cells and smooth muscle layer. But the intensity was not related with the elevated level of serum CK. So, C5b-9 is strongly expressed in the necrotic muscle fiber and blood vessels, and may contribute to the pathogenesis of NM.